RANCANG BANGUN SISTEM INFORMASI LAYANAN PELANGGAN PURNA JUAL BERBASIS WEB PADA PT. COWAY INTERNATIONAL INDONESIA - Muhamad Dhaffa Arofik; Tyzar Sys Ainullah; Bois Yeblo; Sharyanto Sharyanto; Alexius Ulan Bani (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
PT. Coway International Indonesia faces operational constraints in managing customer complaints, which are still handled manually through social media and Excel spreadsheets. This conventional process is prone to data input errors, delays information delivery to technicians, and lacks transparency for customers. This study aims to design and develop a web-based after-sales customer service information system to integrate the workflow digitally. The system was developed using the Waterfall model, implemented with the Laravel framework, and supported by a MySQL database. The developed platform provides specific functionalities, including ticket submission and real-time status tracking for customers, validation by customer service, technician scheduling by staff, and maintenance report inputs by field technicians. The system was validated using Black Box Testing. The results indicate that the system successfully eliminates data redundancy, accelerates response times, and significantly improves the operational efficiency of the company's after-sales services.